Theory and Applications of Economic Indices : Proceedings of an International Symposium Held at the University of Karlsruhe April--June 1976 - Eichhorn, W.; Henn, R.; Opitz, O.; Shephard, R. W. (Wurzburg : Physica-Verlag, 1978)
This volume comprise of proceedings of an International Symposium on Theory and Applications of Economic Indices, held at the University of Karlsruhe April--June 1976.
Includes bibliographical references and index.
lje 24/1/19
Loans
Keywords: Economic inicators; Economics -- Congresses; Conference papers and proceedings